Hepatitis-B Vaccine Response in Inflammatory Bowel Disease Patients: A Systematic Review and Meta-analysis. Issue 10 (4th January 2021) - Kochhar, Gursimran S; Mohan, Babu P; Khan, Shahab R; Chandan, Saurabh; Kassab, Lena L; Ponnada, Suresh; Desai, Aakash; Caldera, Freddy; Dulai, Parambir S; Farraye, Francis A
Abstract: Background: Data on efficacy of hepatitis-B vaccine (HBV) in patients with inflammatory bowel disease (IBD) is limited. Our aim was to review the literature and perform meta-analysis of available studies to quantify efficacy of HBV in patients with IBD. Methods: We conducted a comprehensive search of several databases (inception to July 2020) to identify studies evaluating efficacy of HBV in patients with IBD. Random effects model was used to calculate the pooled rates and I 2 percentage values were used to assess the heterogeneity. Results: A total of 14 studies (2375 patients) were included. Four data sets were available from 2 studies that compared HBV response in patients with IBD against healthy controls. The pooled odds ratio of HBV response in IBD patients was 0.13 (95% CI, 0.05–0.33, P = 0.001). The pooled proportion of adequate immune response (AIR) was 64% (95% CI, 55–72.1, P = 0.003) from 13 data sets, and effective immune response (EIR) was 39.7% (95% CI, 30.7–49.5, P = 0.04) from 10 data sets. Conclusion: Patients with IBD on immunosuppression demonstrated significantly reduced HBV response as compared with general population.